Automotive engineering fundamentals - Stone, Richard, 1955- (SAE International, 2004)
From engines and transmissions to vehicle aerodynamics and computer modeling, the intelligent, interesting presentation of core concepts in Automotive Engineering Fundamentals is sure to make this an indispensable resource for engineering students and professionals alike.